The Development of Homosexual Tendencies's Inventory - Maysitoh Maysitoh; Herman Nirwana; Afdal Afdal (Universitas Negeri Padang, 2020)
Homosexuality is a controversial issue. In general, Indonesian society rejects the existence of homosexuals because they are not in accordance with the prevailing values and norms and are the cause of HIV / AIDS so that it not only endangers individuals and the perpetrators but can also destroy the fabric of society. This is the basis for the need for an instrument to identify a person's sexual orientation. More often than not, homosexual identification tools have been developed abroad so that they are not suitable for the context of Indonesian society. This study aims to develop an instrument capable of measuring the level of a person's homosexual tendency. The research method used follows the steps of developing Gall, Gall, and Borg's model. The research sample used was 265 students. Initially this instrument consisted of 28 items which were analyzed using the IRT approach. The results indicated that the inventory of homosexual tendencies was valid and reliable, totaling 26 items. Thus this instrument can be used to identify levels of homosexual tendencies